2002
DOI: 10.1073/pnas.152456799
|View full text |Cite
|
Sign up to set email alerts
|

Minimum molecular architectures for transcription and replication of the influenza virus

Abstract: The RNA-dependent RNA polymerase of influenza virus is composed of three viral P proteins (PB1, PB2, and PA) and involved in both transcription and replication of the RNA genome. The PB1 subunit plays a key role in both the assembly of three P protein subunits and the catalytic function of RNA polymerization. We have established a simultaneous expression system of three P proteins in various combinations using recombinant baculoviruses, and isolated the PA-PB1-PB2 ternary (3P) complex and two kinds of the bina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 39 publications
2
76
2
Order By: Relevance
“…The observation that PA interacts with PB2 in the absence of PB1 raises an interesting question of whether the PA-PB2 dimer could perform any polymerase activity independent of the intact heterotrimeric complex. Several studies have shown that the PB1-PA binary complex can efficiently synthesize cRNA in the absence of PB2 protein (17,31). Future studies are needed to address the role the PA-PB2 dimer can play in virus polymerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that PA interacts with PB2 in the absence of PB1 raises an interesting question of whether the PA-PB2 dimer could perform any polymerase activity independent of the intact heterotrimeric complex. Several studies have shown that the PB1-PA binary complex can efficiently synthesize cRNA in the absence of PB2 protein (17,31). Future studies are needed to address the role the PA-PB2 dimer can play in virus polymerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…De Novo Initiation via the Internal Initiation of TemplatesWe found that the replication initiation site of the vRNA was located at the second nucleotide of the 3Ј-end, which disagrees with the previous reports (7,22). Therefore, we examined first the initiation nucleotide of v84 using [␥- 32 (Fig.…”
Section: The Effects Of the 3ј Sequences Of The Vrna Templates And Prmentioning
confidence: 70%
“…The replication of the influenza virus is believed to be initiated without primers because the RNA genome (vRNA) purified from the virus was found to possess a terminal triphosphate at the 5Ј-end (30). The purified RdRp heterotrimer was found to initiate transcription from the 3Ј-end of vRNA without primers (7,22). Recently, the internal initiation and primer realignment model of influenza virus replication was proposed by Brownlee and co-workers (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations